Socioterritorial movements. Cases from Latin America and Europe - Halvorsen, Sam; Fernandes, Bernardo Mancano [UNESP]; Valeria Torres, Fernanda (Univ Nac La Plata, Fac Humanidades & Ciencias Educ, 2021)
This paper develops Brazilian geographer Bernardo Mancano Fernandes' notion of socio-territorial movements as an analytical category for social movements that have as their central objective the appropriation of space in pursuit of their political project. It does so by contrasting the concept of socio-territorial movement to those of social movement and sociospatial movement, and proposing four axes of analysis for socio-territorial movements: strategy, identity, political sociability and institutions. These axes are considered across three case studies: the MST in Brazil; an urban social movement from North-West Argentina called the Tupac Amaru Neighborhood Organization; and the 2011 Occupy movement in London. In conclusion, we discuss some key differences between the movements studied, and consider the limits to a socio-territorial analysis.
Keywords: Socio-territorial movements; Territory; MST; Occupy Movement; Argentina